2007
DOI: 10.1021/jf0710027
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Electrothermal Atomization Atomic Absorption Spectrometry Method for Quantification of Total Chromium and Chromium(VI) in Wild Mushrooms and Underlying Soils

Abstract: An ETAAS method was validated to quantify total Cr and Cr VI in mushrooms and the underlying soils. The method includes a sample pretreatment for total Cr dissolution using a wet acid digestion procedure and a selective alkaline extraction for Cr VI . The limits of detection were, expressed in µg/L, 0.15 and 0.17 for total Cr and Cr VI , respectively. The linearity ranges under the optimized conditions were 0.15-25.0 and 0.17-20.0 µg/L for total Cr and Cr VI , respectively. The limits of quantification were, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 16 publications
0
14
1
2
Order By: Relevance
“…In the optimal experimental conditions, limits of detection (LOD) and limits of quantification (LOQ) were calculated according to IUPAC criteria as the concentration corresponding to three times and ten times the standard deviation of ten blank solutions, respectively. These detection limits, even if higher than those previously reported for Cr(VI) determination in foods [10][11][12][13][14], are, to our knowledge, the first ones obtained from an on-line speciation-based analytical protocol.…”
Section: Analytical Figures Of Meritmentioning
confidence: 49%
See 1 more Smart Citation
“…In the optimal experimental conditions, limits of detection (LOD) and limits of quantification (LOQ) were calculated according to IUPAC criteria as the concentration corresponding to three times and ten times the standard deviation of ten blank solutions, respectively. These detection limits, even if higher than those previously reported for Cr(VI) determination in foods [10][11][12][13][14], are, to our knowledge, the first ones obtained from an on-line speciation-based analytical protocol.…”
Section: Analytical Figures Of Meritmentioning
confidence: 49%
“…Soares et al [12] measured total Cr in an alkaline extract of bread, assuming that it was corresponding to Cr(VI) because of the expected precipitation of Cr(III) at this pH. Figueiredo et al did the same for wild mushrooms [13] and Panichev et al [14] for different plant samples. In these studies, Cr(VI) concentrations reported were up to 15 μg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…For the highest doses of fungicides (2RD), copper content in B. bassiana decreased. It is known that fungi are able to accumulate significant amounts of metals (Gadd 1993;Figueiredo et al 2007;Baptista et al 2009), including entomopathogenic fungi (Popowska-Nowak et al 2004;Fomina et al 2005b). Although B. bassiana was able to solubilize copperbased fungicides, and therefore increase copper bioavailability and toxicity, this strain has shown high tolerance to those fungicides, especially to copper hydroxide and copper oxychloride.…”
Section: Resultsmentioning
confidence: 99%
“…Total Cr contents were determined after a microwave assisted digestion of the samples and determination of Cr VI was following the method described by Figueiredo et al [14] Total chromium contents in samples of Chlorophyllum rhacodes, Suillus grevillei, Imleria badia, and Xerocomellus chrysenteron were 0.08 � 0.03, 0.16 � 0.09, 0.09 � 0.07, and 0.17 � 0.16 mg kg À 1 DM, respectively. Total Cr contents were determined after a microwave assisted digestion of the samples and determination of Cr VI was following the method described by Figueiredo et al [14] Total chromium contents in samples of Chlorophyllum rhacodes, Suillus grevillei, Imleria badia, and Xerocomellus chrysenteron were 0.08 � 0.03, 0.16 � 0.09, 0.09 � 0.07, and 0.17 � 0.16 mg kg À 1 DM, respectively.…”
Section: Speciation Of Chromium Oxidation States In Mushroom Fruitingmentioning
confidence: 99%
“…Sarikurkcu et al [6] reported that Lycoperdon perlatum collected from the South Aegean Region in Turkey exceeded legal limits for Pb (as well as for Fe, Mn, Cr, Ni, and Co). Toxic Cr VI contents were measured solely by Figueiredo et al [14] They reported mean contents of total chromium 1.14 and 1.11 mg kg À 1 DM in caps and stalks for 34 samples of 15 mushroom species and mean contents of hexavalent chromium 0.10 and 0.14 mg kg À 1 DM, respectively. [7] Zinc is another metal with high contents in edible mushroom fruiting bodies.…”
Section: Introductionmentioning
confidence: 99%